2014
DOI: 10.1152/japplphysiol.00634.2013
|View full text |Cite
|
Sign up to set email alerts
|

Defining the “dose” of altitude training: how high to live for optimal sea level performance enhancement

Abstract: Chronic living at altitudes of ∼2,500 m causes consistent hematological acclimatization in most, but not all, groups of athletes; however, responses of erythropoietin (EPO) and red cell mass to a given altitude show substantial individual variability. We hypothesized that athletes living at higher altitudes would experience greater improvements in sea level performance, secondary to greater hematological acclimatization, compared with athletes living at lower altitudes. After 4 wk of group sea level training a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
85
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 50 publications
8
85
1
Order By: Relevance
“…These results suggest that,the altitude between 2000 and 2500 m, during the LH-TL protocol, allows an optimal acclimatization response in sea level performance [32].…”
Section: The Determination Of the Aerobic Effort Capacity Parametersmentioning
confidence: 61%
See 1 more Smart Citation
“…These results suggest that,the altitude between 2000 and 2500 m, during the LH-TL protocol, allows an optimal acclimatization response in sea level performance [32].…”
Section: The Determination Of the Aerobic Effort Capacity Parametersmentioning
confidence: 61%
“…The human body can compensate for the lack of O 2 up to an altitude of 5000 m, where the oxygen partial pressure (pO 2 ) reaches [25][26][27][28][29][30][31][32][33][34][35] mmHg, values that represent the minimum limit for survival [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Low to moderate altitude has previously been shown to produce significant improvements in sea level swim time trial performance (~1.9%) [21]. Indeed, in a recent study proclaiming the use of altitudes between 2000-2500 m the authors also found positive physiological (red cell mass volume ~7%,VO 2 ~2%) and performance (~1%) effects for athletes on immediate return to sea level after living at 1754 m [17]; something that is not uncommon at these low altitudes (1200 m) [22]. Performance improvements of this magnitude would indicate meaningful effects for the very elite triathletes involved in this study [23].…”
Section: Methodology Altitudementioning
confidence: 95%
“…A number of studies have suggested an altitude between 2000 and 2500 m is ideal for live-high train-low training, based mainly on the haematological response [8,17]. However recent research suggests athletes can improve performance after altitude training without positive haematological adaptation [18].…”
Section: Methodology Altitudementioning
confidence: 99%
“…Optimizing Altitude for Live High-Train Low (LHTL) Training Chapman et al (2013) hypothesized that athletes living at higher altitudes would experience greater improvements in sea level performance, secondary to greater hematological acclimatization, compared to athletes living at lower altitudes. After 4 weeks of group sea level training and testing, 48 collegiate distance runners (32 men, 16 women) were randomly assigned to one of four living altitudes (1780 m, 2085 m, 2454 m, or 2800 m).…”
mentioning
confidence: 99%